Implementation of Primary Healthcare Services in Community Health Stations in Highly Urbanized City - Gella, Hanna B.; Caelian, Merlita V. (Philippine Social Science Journal, 2021)
Primary healthcare is integral to the Sustainable Development Goal (SDG) of ensuring healthy lives and promoting well-being. A descriptive study assessed the implementation of primary healthcare services in community health stations through a researcher-made questionnaire among healthcare providers and beneficiaries of 30 community health stations. The results revealed that, as a whole, the implementation of primary healthcare services in community health stations is great, with maternal and child healthcare implemented to a very great extent while the treatment of non-communicable diseases to a great extent only. The major challenges encountered are the lack of medical drugs, supplies and equipment, and medical professionals. Primary healthcare has made contributions to the community’s health improvement; however, challenges imply that the quality and efficiency of the services need improvement. The study contributed to new knowledge on implementing healthcare at the lowest level of government, emphasizing patient-centeredness.